Parsing BDD Stories for Automated Verification of Software Artefacts - Silva, Thiago; Fitzgerald, Brian (Electronic Communications of the EASST, 2021)
This position paper reports on our ongoing developments towards the automated verification of software artefacts by parsing sentences on Behaviour- Driven Development (BDD) stories. The solution we propose is based on different strategies for analysing the consistency of user requirements specified in BDD stories on task models, graphical user interfaces (GUIs), GUI prototypes, and domain models. We illustrate our solution through concrete examples and discuss its challenges and limitations.